Use of Remote Sensing in Watershed Development - Ayyangar, R.S.; Tikekar, SS (Journal of Soil and Water Conservation, 2022)
Currently all the activities related to natural resources development and utilization are tackled in an integrated manner in order to realize the full benefit of resources development on sustained basis. The resources development planning and implementation can be efficient and fruitful, if developed on some identifiable and desirable basic unit as done in case of land and water resources development adopting watershed as basic unit. India, perhaps is the best example amongst the developing countries to use watershed as an integrated unit for planning as well as for implementing programmes related to soil and water conservation, drought mitigation, wasteland development, ravine reclamation, tribal welfare, etc.